Transcriptomic analysis of pea plant responses to chitooligosaccharides’ treatment revealed stimulation of mitogen-activated protein kinase cascade - Kozyulina, Polina Yu.; Pavlova, Olga A.; Kantsurova (Rudaya), Elizaveta S.; Bovin, Andrey D.; Shirobokova, Svetlana A.; Dolgikh, Aleksandra V.; Dymo, Alina M.; Dolgikh, Elena A. (Frontiers in Plant Science, 2023)
Since chitooligosaccharides (COs) are water-soluble, biodegradable and nontoxic compounds, their application may be considered as a promising plant-protecting agent. However, the molecular and cellular modes of action of COs are not yet understood. In this study, transcriptional changes in pea roots treated with COs were investigated via RNA sequencing. Pea roots treated with the deacetylated CO8-DA at low concentration (10-5 М) were harvested 24 h after treatment and their expression profiles were compared against medium-treated control plants. We observed 886 differentially expressed genes (fold change ≥ 1; p-value ˂ 0.05) 24 h after treatment with CO8-DA. Gene Ontology term over-representation analysis allowed us to identify the molecular functions of the genes activated in response to CO8-DA treatment and their relation to biological processes. Our findings suggest that calcium signaling regulators and MAPK cascade play a key role in pea plant responses to treatment. Here we found two MAPKKKs, the PsMAPKKK5 and PsMAPKKK20, which might function redundantly in the CO8-DA-activated signaling pathway. In accordance with this suggestion, we showed that PsMAPKKK knockdown decreases resistance to pathogenic Fusarium culmorum fungi. Therefore, analysis showed that typical regulators of intracellular signal transduction pathways involved in triggering of plant responses via CERK1 receptors to chitin/COs in Arabidopsis and rice may also be recruited in legume pea plants.